Mentalization in Chilean Educational Staff With 12-Month-Old Children: Does It Make a Difference in Relation to What Children Receive at Home?. Issue 7 (3rd October 2017) - Farkas, Chamarrita; Strasser, Katherine; Badilla, María Gabriela; Santelices, María Pía
ABSTRACT: Parental mentalizing, which is the capacity to understand behavior in terms of mental states and to reflect this back to a child through speech, is a key construct in child development. Adults with high mentalization promote children's secure attachment, mentalization and self-regulation. This study describes this competency in a sample of teachers from Chilean nurseries in interaction with 12-month-old children during a storytelling scenario and compares it with the children's mothers. The sample comprised 208 adults (104 teachers and 104 mothers). The adults were asked to tell 2 stories to the children, and these situations were recorded, transcribed, and codified using guidelines that identified 4 references to mental states (desires, cognitions, emotions, and attributes) and 4 references to nonmental states (causal and factual talk, physical states, and connections with the child's life). Research Findings : The results showed significant differences between the educational staff and the mothers, and the teachers performed better than the mothers in terms of both greater mentalization and a greater number of references to desires, causal talk, emotions, and physical states. Practice or Policy : The results provide evidence regarding the supportive role played by educational staff in children's development, especially in underprivileged sectors.